Tissue remodeling in Guinea pig lateral prostate at different ages after estradiol treatment - Scarano, W. R.; Cordeiro, R. S.; Goes, R. M.; Carvalho, H. F.; Taboga, SR (Elsevier B.V., 2005)
Estrogen seems to have an essential role in the fibromuscular growth characteristic of benign prostatic hyperplasia (BPH). This paper describes the effects of chronic estradiol treatment on Guinea pig prostatic stroma at different ages. Tissues from experimental animals were studied by histological and histochemical procedures, morphometric-stereological analysis and transmission electron microscopy (TEM). Marked fibromuscular hypertrophy was observed after estradiol treatment in animals of pre-pubertal and adult ages. Increases in the density and thickness of the collagen and elastic fibers were observed by histochemistry. TEM revealed wide distributions of collagen fibrils and large elastic fibers adjacent to the epithelial basal lamina and between the stromal cells, establishing contacts between them. These results indicate that the Guinea pig prostate simulates the stromal modifications observed in BPH in some aged animals after estrogen treatment at different ages, making it a good model for this disease. (c) 2005 International Federation for Cell Biology. Published by Elsevier Ltd. All rights reserved.
Keywords: estradiol; prostate; stroma; collagen fibrils; guinea pig; BPH